ANALYSIS OF THE APPLICATION OF LAVENDER AROMATHERAPY TO REDUCE FATIGUE IN PATIENTS WITH CHRONIC KIDNEY DISEASE (CKD) UNDERGOING HEMODIALYSIS: A CASE STUDY - Sapeni, Muhammad Al-Amin R.; Soraya, Gita Anastasia; Yuniyanti, Tri Ayu; Anwar, Irawati; Yunus, Suwardha; Iwan, Iwan; Bage, Veronika Papo (An Idea Health Journal, 2025)
Chronic kidney disease is a progressive and irreversible condition that leads to a decline in kidney function, requiring renal replacement therapy. The intensive and prolonged treatment process often results in fatigue, which is one of the most common problems in CKD patients undergoing hemodialysis. Elevated urea levels affect erythropoietin production, resulting in decreased red blood cell count or anemia (low hemoglobin levels), leading to energy and protein loss, decreased appetite, nausea, vomiting, and reduced creatinine production—contributing to decreased skeletal energy production, fatigue, and weakness. Despite the frequent pharmacological interventions, fatigue management is often inadequate due to lack of energy, limiting patients' ability to perform therapeutic activities. One of the easiest and most efficient complementary therapies is lavender aromatherapy, which does not interfere with pharmacological treatments. However, it remains underutilized. In 2022, 143 CKD patients in one hospital presented with fatigue complaints, often leading to repeated care episodes. This case study aims to analyze the application of lavender aromatherapy in reducing fatigue levels in CKD patients undergoing hemodialysis.Methods: This study used a case study design with a pre-post test approach involving 3 patients selected through simple random sampling based on inclusion and exclusion criteria. Data were collected through direct observation using the FACIT-Fatigue Scale.Results: The results showed a reduction in fatigue levels in all three patients. Initially, they exhibited severe fatigue. After three days of lavender aromatherapy, fatigue levels decreased to mild. Conclusion: The application of lavender aromatherapy led to a decrease in fatigue levels, suggesting that it can be an effective supportive intervention.